SCIENTIFIC APPROACHES TO DETERMINING THE ESSENCE OF TRANSFER PRICING AND STAGES OF TRANSFER PRICING DEVELOPMENT IN THE WORLD - Kuznyetsov, Oleksandr; Maslov, Vladyslav; Samoilikova, Anastasiia (Socio-economic relations in the digital society, 2025)
Today, the use of transfer pricing by transnational corporations is an established world practice that plays a key role in the formation of global tax policy. The use of transfer pricing mechanisms has a complex impact both on the business structures themselves and on the national economies of the countries within which the relevant corporate entities operate. In an effort to optimize their own financial burden, transnational corporations often resort to strategies that, although they contribute to increasing corporate efficiency, can have negative socio-economic consequences for the jurisdictional countries where the corresponding tax revenues should be accumulated. As a result, there is a threat of deepening financial inequality and a decrease in the level of social protection of the population in these states. Generalization of scientific approaches to the definition of the definitions of “transfer price” and “transfer pricing” made it possible to offer the author’s vision of the categorical apparatus of the study The use of methods of grouping, analysis and synthesis, as well as the method of data interpretation contributed to the specification of the periods of emergence and development of transfer pricing in world practice. The study substantiates a list of commonly used and specific functions inherent in transfer pricing, as well as a list of goals, the achievement of which should be ensured by transfer pricing. The conclusions and recommendations made in the article will be useful to practitioners in the field of taxation, as well as to the heads of transnational corporations or enterprises engaged in foreign economic activity.